Reliability Test of New Questionnaire Designed to Measure Social Wellbeing of Breast Cancer Patients - Neha D Sheth; Vipin D. Naik (Medsci Publications, 2016)
Introduction: Physical, psychological, social and emotional domains are four major elements that affect quality of life of patients with chronic diseases. The study is aimed to examine the reliability of new instrument that has been developed to measure social wellbeing of patients suffering from breast cancer particularly in Indian context. The study has been conducted to understand the impact due to prevalence of various socio cultural norms in Indian society on patients of breast cancer. Method: Reliability is a test to recognize the degree to which an instrument generates consistent results. The internal consistency reliability is tested with the help of Cornbach's Alpha. Result: The new instrument to measure social wellbeing of the breast cancer patients is found to be reliable as value of Cornbach's Alpha is more than 0.75. Conclusion: The Indian social customs generate huge effect on quality of life of patients suffering from chronic disease like cancer. New instrument should be used as a supportive instrument to measure an important dimension "social wellbeing" of the quality of life of breast cancer patients in detail particularly in Indian context.